Discordance between Genexpert, Line Probe Assay and Drug Susceptibility Test in Assessing Drug-Resistant Tuberculosis - Tutik Kusmiati1 , Kristin Purnama Dewi2 , Yulia Devina Suci2 , Soedarsono3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Rapid molecular diagnostics have potentially revolutionized early detection of drug-resistanttuberculosis (DR-TB) in Indonesia. However, there is discordance between conventional culture usingdrug susceptibility test (DST) and rapid diagnostic tools using GeneXpert and line probe assay (LPA).This discordance result can cause confusion to clinician in determining diagnosis of DR-TB. Objective:This study aimed to identify discordance between GeneXpert, LPA, and DST. Methods: A retrospectivestudy was conducted at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Data were collectedbased on medical record between third to fourth quarter of 2018. Rifampicin resistant-tuberculosis (RR-TB)proven by GeneXpert, were further analyzed with second-line LPA and DST. Discordance result betweenit was analyzed using McNemar. Results: Among 81 patients diagnosed with DR-TB, 59 patients RR-TBwere eligible in this study. There were 13 (22.0%) DST rifampicin result showed sensitive but resistantto GeneXpert. Among 53 samples from LPA, there were 3 (5.7%) result showed LPA fluoroquinoloneresistant but sensitive to DST ofloxacin; 10 (18.9%) result has LPA fluoroquinolone sensitive but resistantto DST ofloxacin; 2 (3.8%) has LPA second-line injectable drug (LPA SLID) resistant but sensitive to DSTkanamycin; 5(9.4%) has LPA SLID sensitive but resistant to DST kanamycin. The McNemar analysis showeddiscordance between GeneXpert and DST rifampicin was 13 (22.0%; p=0.046); LPA fluoroquinolone andDST ofloxacin was 13 (24.6%; p=0.042); LPA SLID and DST kanamycin was 7 (13.2%; p=0.183). Novariable that can be used to analyze discordance result between GeneXpert and LPA. Conclusion: Thereis significant discordance between GeneXpert and DST; LPA fluoroquinolone and DST ofloxacin, whileneither LPA SLID nor DST kanamycin shows no significant discordance.